The Impact of the Independent Board of Commissioners' Supervisory Mechanism on the Relationship Between Intellectual Capital and Banking Performance - Gunawan, M.A. Andrew; Susetyo, Didik; Fuadah, Luk Luk; Wahyudi, Tertiarto (AIBPM Publisher, 2024)
This research delves at the role of Indonesia's Independent Board of Commissioners (IBC) in strengthening corporate governance systems and how it affects the relationship between IC and the efficiency of the country's banks. In recent years, IC has emerged as a critical differentiator in the banking sector., especially in a financial services environment that heavily relies on knowledge and technology, including digitalization. The utilization of IC, supported by an effective IBC supervisory mechanism, can optimize banking performance. From 2019 through 2023, 124 banks meeting the requirements are used to analyze the banking industry. The findings of this study show that the impact of Indonesia's independent board of commissioners on the correlation between IC and bank performance is substantial.